The Role of Cultural Heritage in Modern World Politics - T. M. Balmatova (Vestnik MGIMO-Universiteta)
Book review: Christofoletti R., Botelho M. L. (ed.) 2021. International Relations and Heritage. Patchwork in Times of Plurality. Springer Nature Switzerland AG. 468 p. DOI: 10.1007/978-3- 030-77991-7